Controle do reservatório canino para leishmaniose visceral, na regional noroeste de Belo Horizonte, Minas Gerais, 2006-2011 - Stefanne Aparecida Gonçalves (2013)
Was conducted a descriptive study with the objective of to describe the occurrence of canine visceral leishmaniasis, in the Northwest Regional in Belo Horizonte, from 2006 to 2011. Data regarding with the canine control were obtained from the Municipal Secretariat of Health. From a total of 151.725 tests, 86.1% were negative, 7.4% were positive, 2,1% were undetermined and 3.8% were monitor. The expansion of the disease along the period was evident. There was an increase of the coverage of census surveys and a decrease in the tests requested by residents, followed by decreasing of the canine prevalence in areas covered in the period. The undetermined results also have declined, while serologies "monitor" have increased. The seroconversion rate among dogs undetermined was 54.3%, occurring in 104 days on average, with a median of 54 days. It was found that 98, 1% of the samples were collected on filter paper and the laboratory diagnosis was delivered in 18.1 days on average, after the blood collection. The infected dogs removal happened about 51.7 days on average, with median of 39 days. The positive dogs withdrawal was 86.6%, which was negatively impacted by refusals, which represented 7.8% over the period, ranging from 1.9% to 15.6%. It is necessary to intensify the activities of health education in order to alert citizens about the dogs importance in the infection transmission dynamics and thereby increase the population adherence to the Visceral Leishmaniasis Control Program. The database of the Information System for Zoonosis Control of Belo Horizonte was conducive to study the expansion and the combat of the disease in the city. Thus, it is recommended that it receives periodic maintenance, with quality monitoring, so that further studies might be performed.